2021
DOI: 10.1111/gfs.12538
|View full text |Cite
|
Sign up to set email alerts
|

Re‐ensiling effects on sorghum silage quality, methane emission and sheep efficiency in tropical climate

Abstract: The objective of the present study was to evaluate whether sorghum silage exposure to air for 8, 16 or 24 hr before re‐ensiling reduces silage quality and animal feed efficiency. Sorghum was ensiled in 52 metal drums (13 for each exposure time) with 200‐L capacity, and after 112 days, 39 drums were opened and silage was exposed to air for 8, 16 or 24 hr. Thirteen silos were not opened and considered control treatment. Subsequently, silage was re‐ensiled, and after 56 days, all silos were opened to determine si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…dos Anjos et al (2018) exposed inoculated and re‐ensiled sorghum to air for 12 h and verified a reduction in ammonia and lactic acid and an increase in propionic acid. Santos et al (2021) analysed re‐ensiled sorghum after exposure to air for 8, 16, and 24 h and found a linear regression increase in butyric acid and N‐NH 3 .TN −1 . de Lima et al (2016) verified a linear regression increase for pH when studying re‐ensiled corn for 12, 24, and 48 h.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dos Anjos et al (2018) exposed inoculated and re‐ensiled sorghum to air for 12 h and verified a reduction in ammonia and lactic acid and an increase in propionic acid. Santos et al (2021) analysed re‐ensiled sorghum after exposure to air for 8, 16, and 24 h and found a linear regression increase in butyric acid and N‐NH 3 .TN −1 . de Lima et al (2016) verified a linear regression increase for pH when studying re‐ensiled corn for 12, 24, and 48 h.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al (2021) studied intake, digestibility, methane emission, and energy losses in sheep, and observed that silage re‐ensiled after 24 h did not affect animal efficiency. Overall, data on intake, apparent digestibility, and feeding behaviour of animals treated with inoculated and re‐ensiled material remains incipient in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Some microbial inoculants have been used to reduce possible nutritional and dry matter (DM) losses due to re-ensiling. Studies on the effect of reensiling and microbial inoculant use are recent (Chen and Weinberg, 2014;Michel et al, 2017;Dos Anjos et al, 2018;Santos et al, 2021). More information is needed regarding the re-ensiling process and microbial inoculants use containing Lactobacillus plantarum and Propionibacterium acidipropionici on the maize silage quality.…”
Section: Introductionmentioning
confidence: 99%